2000
DOI: 10.1111/j.1469-7793.2000.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in muscle strength, muscle fibre size and myofibrillar gene expression after immobilization and retraining in humans

Abstract: Changes in muscle strength, vastus lateralis fibre characteristics and myosin heavy‐chain (MyoHC) gene expression were examined in 48 men and women following 3 weeks of knee immobilization and after 12 weeks of retraining with 1866 eccentric, concentric or mixed contractions. Immobilization reduced eccentric, concentric and isometric strength by 47 %. After 2 weeks of spontaneous recovery there still was an average strength deficit of 11 %. With eccentric and mixed compared with concentric retraining the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
209
6
16

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(251 citation statements)
references
References 50 publications
20
209
6
16
Order By: Relevance
“…Comparable evidence of a preferential or more pronounced type II fibre hypertrophy in response to heavy resistance training has been reported previously (e.g. Hather et al 1991;Roman et al 1993;Volek et al 1999;Kadi et al 1999;Andersen & Aagaard, 2000;Hortobagyi et al 2000). Apparently, type II muscle fibres seem to possess a greater adaptive responsiveness to the intense muscle-loading regimes associated with heavy-resistance training.…”
Section: Figuresupporting
confidence: 65%
“…Comparable evidence of a preferential or more pronounced type II fibre hypertrophy in response to heavy resistance training has been reported previously (e.g. Hather et al 1991;Roman et al 1993;Volek et al 1999;Kadi et al 1999;Andersen & Aagaard, 2000;Hortobagyi et al 2000). Apparently, type II muscle fibres seem to possess a greater adaptive responsiveness to the intense muscle-loading regimes associated with heavy-resistance training.…”
Section: Figuresupporting
confidence: 65%
“…This is contrasted by the fact that the elderly population more often undergoes periods of immobilization and disuse, not only due to joint pain, but also due to a higher degree of comorbidity and hospitalization (32). Studies in healthy young adults have demonstrated that immobilization leads to rapid decreases in maximal muscle strength, muscle mass, and neural activation (4,19); however, recent studies indicate that skeletal muscle in aged animals and humans is more vulnerable to muscle unloading than that in young individuals (8,41). Furthermore, recent data from Yasuda et al (43) show that there might be a gender-specific response to unloading, as evidenced by a more pronounced decrease in specific strength in young women compared with young men after 14 days of unilateral limb immobilization.…”
mentioning
confidence: 99%
“…Originally utilized as a paradigm for studying muscle damage, recent research suggests that controlled application of negative work is a potent stimulus for increasing muscle size and strength, which are the predominant impairments following ACL-R. Hortobagyi et al 10 compared a 12-week ECC versus concentric (CON) resistance training program via an isokinetic dynamometer after 3 weeks of knee immobilization on healthy college-age men and women. Improvements in muscle size in the ECC group were nearly double those of the CON group.…”
mentioning
confidence: 99%